Effect of bap and sucrose on the development of cormel in mukhi kachu (Bangladesh Journal of Agricultural Research, 2016)
In vitro cormel development in Mukhi Kachu (Colocasia esculenta) Var. Bilashi was assessed in an experiment using three levels of BAP (0, 5 and 10 mg/l) and four levels of sucrose (0, 5, 10 and 15 %). Individual shoot excised from multiple shoot was used as explant in this experiment. In vitro cormel formation of Colocasia is an important means of organogenesis, which initiated earlier with 10% sucrose in 15% culture, whereas 15% sucrose produced cormels in 50% culture. While BAP at 10 mg/l formed cormels in 32.5% cultures but these two factors together formed cormels in 85% cultures, having 2.5 cormel per culture. The cormel weighed upto 1.7 g and contained 81.5% dry matter.Bangladesh J. Agril. Res. 40(4): 601-606, December 2015